The effects of auditor reputation, financial condition, and potential intensive economy on artificial auditor rotation - Junaidi, Junaidi; Hartadi, Bambang; Sajarwo Yurianto, Priyo; Nurdiono, Nurdiono (Universitas Hayam Wuruk Perbanas, 2015)
This research empirically re-tests the effects of auditor reputation, client’s financial condition, and potential intensive economy on artificial auditor rotation. The issue of audit quality is still interesting for the researchers to empirically. Auditors are demanded to execute their profession independently. To maintain their being independent, this profession is regulated in the Decree by the Minister of Finance No.17/PMK.01/2008 on public accountant service. It is mandatory for auditor rotation in that regulation and this is interesting to study more profoundly because in Indonesia this phenomenon of artificial rotation is found. Artificial auditor rotation indicates a condition in which, conceptually, there has been a change of the auditor but substantially the relationship between the auditor and the client is still going on. This research uses sample of companies listed in Indonesia Stock Exchange in 2002-2011, by purposive sampling technique. The analysis of the research was done using logistic regression. The results of the research show that auditor reputation affects auditor rotation. Yet, company’s financial condition and potential incentive economy do not affect auditor rotation. This research is expected to deepen the concept of audit quality, whereas in practice it is expected to provide inputs for regulating auditor rotation. Auditors are expected to show real auditor rotation.